The Impact of Storytelling-Based Teaching Material Module Toward Folklore Writing Skills - Dessy Wardiah; Hetilaniar Hetilaniar; Dian Nuzulia Armariena; Liza Murniviyanti (STAI Hubbulwathan Duri, 2022)
The purpose of this study was to see how the storytelling-based teaching material module affected the ability to write folklore. The research method used is a posttest control design, which means that there is treatment in both the control and experimental classes. The study was carried out at the Indonesian Language Education Study Program, Faculty of Teacher Training and Education, PGRI Palembang University. To assess students' writing abilities, data was collected using an essay test. A t-test was used to analyze the data. According to the calculations, the Paired Sample t-test = 0.029 Significant Level = 0.05. As a result, it is known that the group of students (control class) who did not receive the learning treatment with the storytelling-based writing teaching materials module had a lower mean value than the group of students who used the storytelling-based writing teaching module during the learning process. Meanwhile, the experimental class had a Paired Sample t-test value of 0.188 Significant Level = 0.05. As a result, it is known that the group of students (control class) who did not receive learning treatment with the storytelling-based writing module scored higher on average than the group of students who did not use the storytelling-based writing module in class.